Psychosocial Impact of COVID-19 on Healthcare Workers - Yazdanfar, Maryam; Bachuwa, Ghassan; Rios-Bedoya, Carlos; Khaneki, Sina (International Journal of Psychosocial Rehabilitation, 2024)
COVID-19 pandemic has significantly impacted frontline workers over the past year. It is essential to evaluate the psychosocial impact of this pandemic on Healthcare workers to minimize the negative impacts of this pandemic as well as potential pandemics in the future in this group. Many of these individuals have been experiencing high levels of stress and symptoms of both anxiety and depression. This is exceptionally worrisome as if left untreated, can lead to long-term mental health problems. Since December 2019, many people have been infected with the coronavirus around the world. Today, there are more than140millionconfirmed cases of coronavirus globally, with more than three million deaths as a result of this disease (COVID-19 situation update worldwide, 2020). In many ways, this virus has caused fear, stress, anxiety, and adverse psychosocial impacts. The National Health Commission of China has released multiple reports about the mental health crisis related to coronavirus and its negative emotional, psychological, and social impacts on the medical workers (Kang et al., 2020). According to a recent article by Lai et al., there is a great concern on social and mental pressures on healthcare professionals during an outbreak. Other recent study suggested that compare to the general population, healthcare workers were more likely to experience the burden of depression, mainly because of fear of getting infected and passing it on to their family members and loved ones, lack of personal protective equipment, and working too many hours during the COVID19 pandemic (Krishnamoorthy et al., 2020).Previous reports have shown that in similar events in the past such as sever acute respiratory syndrome(SARS) and Middle East respiratory syndrome (MERS) outbreaks, healthcare professionals experienced a great level of anxiety, fear, mental pressure, and symptoms of depression even after control of the outbreak. Moreover, recent data have shown the most underestimated problem during this pandemic is every day increase of workload on healthcare professionals which can be triggered to developing anxiety and psychiatric disorders (DelgadoGallegos et al., 2020). In a study by Wang et al., during the initial phase of an outbreak across China, more than half of participants reported as experiencing a moderate to severe psychological impact and with over a third of them showed signs of moderate to severe anxiety. At this time, the main focus of public health departments and the World Health Organization is on how to prevent the spread of COVID-19 and protect our healthcare workers from exposure. Therefore, further research is necessary to study the pandemic’s holistic impacts and look into ways to promote mental wellbeing among healthcare workers. The objective of our study is to evaluate the impact of COVID-19 on healthcare workers at Hurley Medical Center and identify individuals at highest risk to establish preventative interventions to ameliorate the negative impact of similar events on the vulnerable population in the future.